2015
DOI: 10.1590/0100-2945-163/14
|View full text |Cite
|
Sign up to set email alerts
|

Correlações Genéticas E Análise De Trilha Para Caracteres De Fruto Da Palmeira Juçara

Abstract: RESUMO -A palmeira Euterpe edulis é uma espécie nativa da Mata Atlântica e atualmente se encontra na lista das espécies ameaçadas de extinção. Uma alternativa para retirá-la desta lista seria o estímulo para o plantio comercial, focando o manejo dos frutos, que recebem a classificação de "superfruta" pelas suas propriedades químicas e nutricionais. Entretanto, uma etapa de extrema importância que precede a seleção de genótipos superiores é o estudo das associações entre as variáveis, pois permite traçar estrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A sample of fruits was taken from each genotype, packed in properly identified plastic bags and transported to the Plant Biometry laboratory at the Federal University of Espı ´rito Santo, where morphometric evaluations of fruits and seeds were carried out in a completely randomized design. For EDF, data were measured in millimeters (mm) obtained using a 6" digital caliper (Zaasprecision1), performed on five fruits individually, as recommended by Marc ¸al et al (2015) [30], who observed high repeatability values for these characteristics. The authors concluded that five measurements are necessary to carry out the measurement to reach coefficients of determination of 95%.…”
Section: Plos Onementioning
confidence: 99%
“…A sample of fruits was taken from each genotype, packed in properly identified plastic bags and transported to the Plant Biometry laboratory at the Federal University of Espı ´rito Santo, where morphometric evaluations of fruits and seeds were carried out in a completely randomized design. For EDF, data were measured in millimeters (mm) obtained using a 6" digital caliper (Zaasprecision1), performed on five fruits individually, as recommended by Marc ¸al et al (2015) [30], who observed high repeatability values for these characteristics. The authors concluded that five measurements are necessary to carry out the measurement to reach coefficients of determination of 95%.…”
Section: Plos Onementioning
confidence: 99%
“…Published scientific studies evaluating associations between Euterpe edulis traits are scarce in the literature (Marçal et al, 2015;Oliveira et al, 2015;Silva et al, 2018). However, these analyzes are fundamental for understanding the interactive behavior between traits, revealing linear cause and effect responses that are essential for the agricultural development of the crop and for breeding programs, as it allows the determination of different types of practical strategies.…”
Section: Genetic Parameters Genetic Correlation and Phenotypic Correl...mentioning
confidence: 99%
“…A sample of fruits was taken from each matrix, packed in properly identified plastic bags and transported to the Plant Biometry laboratory at the Federal University of Espírito Santo, where morphometric evaluations of fruits and seeds were carried out in a completely randomized design. For EDF, data were measured in millimeters (mm) obtained using a 6" digital caliper (Zaasprecision®), performed on five fruits individually, as recommended by Marçal et al (2015) who observed high repeatability values for these characteristics. The authors concluded that five measurements are necessary to carry out the measurement to reach coefficients of determination of 95%, measurements above this amount increase costs and evaluative time, bringing little additional information to the works.…”
Section: Phenotyping Of Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixed-models method has been used to generate information in selective-breeding programs for perennial species such as sugarcane , açaí (Euterpe oleracea) (TEIXEIRA et al, 2012), juçara (Euterpe edulis) (MARÇAL et al, 2015), guava (SANTOS et al, 2017), and passion fruit (SANTOS et al, 2015;SILVA et al, 2016).…”
Section: Introductionmentioning
confidence: 99%